PREVALENCE OF ANTIBODIES ANTI-Babesia IN CATTLE IN THE NORTH PLATEAU OF SANTA CATARINA (Revista de Ciências Agroveterinárias, 2002)
With the aim to determine the prevalence of antibodies anti-Babesia bigemina and anti-Babesia bovis, samples were collected in sterile tubes from the jugular vein and sera examined from 388 bovines from dairy breeds of both sexes in 16 farms, in counties on the north plateau of Santa Catarina. The samples were grouped recording to age range as following: group 1, from three to six months; group 2, from six to twelve months; group 3, from twelve to eighteen months; group 4, from eighteen to twenty four months, and group 5, more than twenty four months. The sera obtained were examined by the Indirect Immunofluorescence Reaction (RIFI) for Babesia. Positive reactions were those which presented fluorescence at the serum dilution of 1:160. The results were tabulated and submitted to statistical analysis using Chi-Square test. From the 388 samples analyser 76,8% were positive for B. bovis and 84,5% were positive for B. bigemina.
Keywords: Prevalence of antibodies; Babesia bigemina; Babesia bovis; bovines